2020
DOI: 10.2337/figshare.12970550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Empagliflozin on Obstructive Sleep Apnea, Cardiovascular, and Renal Outcomes: An Exploratory Analysis of the EMPA-REG OUTCOME Trial

Abstract: <b>Objective: </b>To explore the effects of empagliflozin on the incidence of obstructive sleep apnea (OSA) and its effects on metabolic, cardiovascular (CV), and renal outcomes among participants with or without OSA in the EMPA-REG OUTCOME trial. <p><b>Research Design and Methods: </b>Participants with diabetes and CVD were randomized to empagliflozin (10/25mg), or placebo daily in addition to standard of care. OSA was assessed by investigator-reports using MedDRA-18.0 and CV o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Preliminary results of their administration in patients with OSAS and T2D suggested not only important metabolic benefits but also significant improvements in apnoea hypopnoea index (AHI), hypoxaemia during sleep, and excessive daytime sleepiness [132,133]. A recent exploratory post-hoc analysis of the EMPA-REG OUTCOME trial suggested that approximately 6% of participants had OSAS at baseline, and that patients with OSAS experienced higher overall all-cause mortality, as well as cardiovascular and kidney events, confirming the huge cardiorenal burden that characterize this population [134,135]. A trend towards enhanced empagliflozin activity upon weight loss (adjusted for baseline body weight) in patients with OSAS, compared to those without OSAS, was also found.…”
Section: Osasmentioning
confidence: 97%
“…Preliminary results of their administration in patients with OSAS and T2D suggested not only important metabolic benefits but also significant improvements in apnoea hypopnoea index (AHI), hypoxaemia during sleep, and excessive daytime sleepiness [132,133]. A recent exploratory post-hoc analysis of the EMPA-REG OUTCOME trial suggested that approximately 6% of participants had OSAS at baseline, and that patients with OSAS experienced higher overall all-cause mortality, as well as cardiovascular and kidney events, confirming the huge cardiorenal burden that characterize this population [134,135]. A trend towards enhanced empagliflozin activity upon weight loss (adjusted for baseline body weight) in patients with OSAS, compared to those without OSAS, was also found.…”
Section: Osasmentioning
confidence: 97%
“…We read with great interest the leading article by Neeland et al (1) highlighting the beneficial effects of empagliflozin treatment on several metabolic end points among participants with type 2 diabetes and obstructive sleep apnea (OSA) in the BI 10773 (Empagliflozin) Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME). In addition, the authors observed a lower frequency of new-onset OSA, even when adjusting for baseline BMI.…”
mentioning
confidence: 99%